2009
DOI: 10.1111/j.1524-4733.2008.00446.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effectiveness Model Comparing Endovascular Repair to Open Surgical Repair of Abdominal Aortic Aneurysms in Canada

Abstract: Based on commonly quoted willingness-to-pay thresholds, EVAR was not found to be cost-effective compared to OR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 24 publications
1
39
0
Order By: Relevance
“…This is comparable to findings of most previous modelling studies of the expected cost-effectiveness of ultrasound screening programmes for AAA, which concluded that they would generally cost less than ¤20 000 per life-year saved 18,57,58 . However, models vary and it is difficult to attribute differences in results to country-specific assumptions based on the reported data.…”
Section: Discussionsupporting
confidence: 89%
“…This is comparable to findings of most previous modelling studies of the expected cost-effectiveness of ultrasound screening programmes for AAA, which concluded that they would generally cost less than ¤20 000 per life-year saved 18,57,58 . However, models vary and it is difficult to attribute differences in results to country-specific assumptions based on the reported data.…”
Section: Discussionsupporting
confidence: 89%
“…9,23,31 However, other studies have also assumed an equal survival after a specific time period or assumed that the initial benefit of EVAR continued without any convergence (catch up) in survival. 42 Most previous economic evaluations have reported that the total costs of EVAR were higher than those of OSR, 6,10,31,32,38e40,42,43 mainly owing to the higher device costs. However, in four studies EVAR was considered cost saving as the initial admission costs of EVAR were lower than those of OSR owing to a reduction in length of hospital stay.…”
Section: Discussionmentioning
confidence: 98%
“…With the exception of a few studies, EVAR has not been found cost-effective compared to OSR which may be due to the fact that many randomized or observational studies do not explicitly separate out OSR patients based on presurgical risk. For example, our own 10-year decision analytic model populated with clinical data derived from a systematic literature and cost data from the field evaluation indicated that at an incremental cost of more than $400,000 per life year gained, EVAR was not cost-effective compared to OSR in Canada [12]. In this paper, the 30-day mortality rate derived from a systematic literature review was 1.5% for EVAR (compared to 0.7% in our study) and 4% for OSR (compared to 1.4% in low risk patients and 9.6% in high risk patients receiving OSR).…”
Section: Discussionmentioning
confidence: 99%